Post-Lie Algebras and Isospectral Flows - Ebrahimi-Fard, K.; Lundervold, A.; Mencattini, I.; Munthe-Kaas, H.Z. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
In this paper we explore the Lie enveloping algebra of a post-Lie algebra derived from a classical R-matrix. An explicit exponential solution of the corresponding Lie bracket flow is presented. It is based on the solution of a post-Lie Magnus-type differential equation.